Replies - Tappolet, Christine (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
This text consists in replies to the commentaries on my book, Philosophy of Emotion: A Contemporary Introduction.